‘JAFFA’ SWEET ORANGE PLANTS GRAFTED ONTO FIVE ROOTSTOCKS - ELÍDIO LILIANO CARLOS BACAR; CARMEN SILVIA VIEIRA JANEIRO NEVES; RUI PEREIRA LEITE JUNIOR; INÊS FUMIKO UBUKATA YADA; ZULEIDE HISSANO TAZIMA (Revista Brasileira de Fruticultura, 2017)
ABSTRACT Low genetic diversity of citrus scion and rootstock cultivars makes the crop more vulnerable to diseases and pests. The objective of this study was to evaluate the performance of ‘Jaffa’ sweet orange grafted onto five rootstocks over six harvests in subtropical conditions in the north of Paraná state, Brazil. The experiment used a randomized block design, with six replications and two trees per plot, spaced at 7.0 m x 4.0 m. The rootstocks were: ‘Rangpur’ lime, ‘Cleopatra’ and ‘Sunki’ mandarins, ‘Fepagro C-13’ citrange, and ‘Swingle’ citrumelo. The variables evaluated were vigor, yield, and yield efficiency of the trees as well as the physical and chemical characteristics of the fruits. Data were subjected to analysis of variance, complemented by Scott-Knott test at 5% probability. The smallest tree canopy for ‘Jaffa’ sweet orange plants was induced by the ‘Rangpur’ lime rootstock. The trees had the same cumulative yield performance over six seasons for all rootstocks. The best yield efficiency for ‘Jaffa’ sweet orange trees was provided by ‘Fepagro C-13’ citrange rootstock. With regard to fruit quality, no differences were observed among the rootstocks and the ‘Jaffa’ sweet orange fruits met the standards required by the fresh fruit market and the fruit processing industry.